I golosi: el contrapasso y los sentidos en el “Purgatorio” dantesco - Jarilla Bravo, Salud María (Revista de Filología Románica, 2008)
In this article I will examine the importance of senses within the concept of contrappasso. While living beings, the gluttons exceeded in drinking and eating and are now condemned to the most atrocious starvation. The vision of a tree bearing plenty of fruits and water, which they cannot reach, increases the souls’ sufferance in that it makes their appetite grow.